Natural Killer T-Cell Agonist α-Galactosylceramide and PD-1 Blockade Synergize to Reduce Tumor Development in a Preclinical Model of Colon Cancer - Wang, Ying; Bhave, Madhura S.; Yagita, Hideo; Cardell, Susanna L. (Frontiers in Immunology, 2020)
Murine and human invariant natural killer T (iNKT) lymphocytes are activated by α-galactosylceramide (α-GalCer) presented on CD1d. α-GalCer was first described as a lipid that had strong anti-metastatic effects in a mouse melanoma model, and it has subsequently been shown to induce efficient iNKT cell dependent tumor immunity in several tumor models. We have shown that α-GalCer treatment leads to a weak reduction of polyp burden in the autochthonous ApcMin/+ mouse model for human colon cancer, however this treatment resulted in upregulation of the inhibitory receptor PD-1 on iNKT cells. While anti-PD-1 treatment can prevent immune-suppression in other cancer types, human colon cancer is generally resistant to this treatment. Here we have used the ApcMin/+ model to investigate whether a combined treatment with α-GalCer and PD-1 blockade results in improved effects on polyp development. We find that PD-1 expression was high on T cells in polyps and lamina propria (LP) of ApcMin/+ mice compared to polyp free Apc+/+ littermates. Anti-PD-1 treatment alone promoted Tbet expression in iNKT cells and CD4 T cells, but did not significantly reduce polyp numbers. However, the combined treatment with anti-PD-1 and α-GalCer had synergistic effects, resulting in highly significant reduction of polyp numbers in the small and large intestine. Addition of PD-1 blockade to α-GalCer treatment prevented loss of iNKT cells that were skewed towards a TH1-like iNKT1 phenotype specifically in polyps. It also resulted in TH1 skewing and increased granzyme B expression of CD4 T cells. Taken together this demonstrates that a combination of immune stimulation targeting iNKT cells and checkpoint blockade may be a promising approach to develop for improved tumor immunotherapy.